2011
DOI: 10.1371/journal.pone.0026866
|View full text |Cite
|
Sign up to set email alerts
|

KIAA0101 Is Overexpressed, and Promotes Growth and Invasion in Adrenal Cancer

Abstract: BackgroundKIAA0101 is a proliferating cell nuclear antigen-associated factor that is overexpressed in some human malignancies. Adrenocortical neoplasm is one of the most common human neoplasms for which the molecular causes are poorly understood. Moreover, it is difficult to distinguish between localized benign and malignant adrenocortical tumors. For these reasons, we studied the expression, function and possible mechanism of dysregulation of KIAA0101 in human adrenocortical neoplasm.Methodology/Principal Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 28 publications
(54 reference statements)
10
56
0
Order By: Relevance
“…We found that KIAA101 was significantly overexpressed at both the mRNA and protein levels in ccRCC, similarly to other cancers. In line with previous reports, we found that knockdown of KIAA0101 led to reduced migration and invasion ability of kidney cells but did not affect the cell proliferation similarly to adrenal cancer (31 ). In several cell types, proliferation and migration/invasion are distinct, supporting the "go or grow" hypothesis (32 ).…”
Section: Discussionsupporting
confidence: 92%
“…We found that KIAA101 was significantly overexpressed at both the mRNA and protein levels in ccRCC, similarly to other cancers. In line with previous reports, we found that knockdown of KIAA0101 led to reduced migration and invasion ability of kidney cells but did not affect the cell proliferation similarly to adrenal cancer (31 ). In several cell types, proliferation and migration/invasion are distinct, supporting the "go or grow" hypothesis (32 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we proved that NS5ATP9 prevented LX-2 cells from proliferation and migration, and promoted apoptosis, which differs entirely from its proliferative and anti-apoptotic activities in most types of tumor cells [10,14,28,29], but is consistent with that in others, including HCC [30,31]. The promotion/suppression effects of NS5ATP9 on HSC apoptosis/proliferation may be one of the ways to protect HSCs from maintaining the activation status.…”
Section: Discussionsupporting
confidence: 68%
“…(iii) Results of aCGH analysis revealed that KIAA0101 knockdown altered gene copy numbers, which could affect gene expression. These genes include MAPK, 15 BCL-2, 16 and MAL, 17 which has been shown in previous studies 10,13,14 to be altered in EC. In addition, several previously unreported genes (such as LY6K, MFAP5, HOXC9, TNFRSF12A, DHRS2, FST, and GPX3) were also found to be differentially expressed in KIAA0101-knocked-down esophageal cells, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 72%
“…13 KIAA0101 enables tumor progression in several cancer types. 14 Our previous study showed that the KIAA0101 protein was elevated in gastric cancer tissues and promoted tumor cell proliferation, invasion, and served as a biomarker for prediction of early tumor recurrence. 10 However, earlier studies of KIAA0101 expression in EC did not reveal such a role of KIAA0101 in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 99%